Applying Quizziz in Online English Learning: How It Improves Intrinsic Motivation - Aisha Tallita Ramadhan Predyasmara; Vega Hesmatantya; Waode Hamsia (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2022)
increase students' intrinsic motivation in learning English and find out how students respond to the use of Quizizz in teaching English during Covid 19. The researcher used Classroom Action Research (CAR) as the research design. The researcher analyzed qualitative and quantitative data, which came from observation, questionnaires, and interviews conducted in the last cycle to know the improvement of students' intrinsic motivation and responses. This study showed that Quizizz live lessons can increase students' intrinsic motivation in learning English. This was proven by the mean score acquired from the student's intrinsic motivation inventory questionnaire, which was 3.28 in the pre-cycle. This score improved to 3.63 in cycle 1 and even higher in cycle 2, which is 4.60. The qualitative data, based on finding the students' responses to Quizzes, showed that most students were interested in and enjoyed learning English through the Quizziz platform Quizziz platform is improving students' intrinsic motivation in learning English online classes in the Pandemic Era.Â